St. Vincent de Paul [videorecording] - Family Rosary Crusade (Quezon City : Felta.)
Vincent was born in France in 1576. When he was still a young priest, he was captured by Turkish pirates who sold him into slavery. For 2 years he had to work hard for the masters who bought him. He converted his last master and was then set free. Vincent was sent to work in a parish near Paris. He was a very great friend of the poor. He started groups to look after them. The women took care of the sick and cooked meals for them. Men gave food and clothes to the needy. Vincent started the Order of the Daughters of Charity who worked for the poor and sick. He built homes for the poor, the sick, the aged and the abandoned children. He also started the Congregation of the Mission, a society of priest and missionaries called the Vincentians. Vincent died in Paris at age of 84. The Saint Vincent De Paul Society continues his work for the poor.
Keywords: Religion -- Philippines; Saint -- Philippines